Independensi, Etika Profesi, Integritas dan Kinerja Auditor KAP di Bali - Kemarayanthi, Desak Made; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 33 No 2 (2023), 2023)
Auditor performance is the ability of an auditor to produce financial audits within a certain period of time. Professional audit services that are independent, adhere to professional ethics and have high integrity are needed to get good auditor performance and be trusted by the public. The research aims to determine the Effect of Independence, Professional Ethics and Integrity on Auditor Performance. The research was carried out at a Public Accountant Office in the Province of Bali and has been registered in the IAPI directory with a population of 122 auditors and a sample of 57 respondents. Research using multiple linear regression analysis. The results of the study show that independence, professional ethics and integrity have a positive effect on auditor performance. This shows that the higher the attitude of independence and integrity and adherence to professional ethics can make the resulting auditor's performance increase. Keywords: Independence; Professional ethics; Integrity; Auditor Performance